Arthroscopic Treatment and Outcomes of Borderline Dysplasia With Acetabular Retroversion: A Matched-Control Study From the MASH Study Group. Issue 8 (July 2021) - Matsuda, Dean; Kivlan, Benjamin R.; Nho, Shane J.; Wolff, Andrew B.; Salvo, John P.; Christoforetti, John J.; Martin, RobRoy L.; Carreira, Dominic S.
Background: Although acetabular retroversion (AR) occurs in dysplasia, management of the crossover sign (COS) or outcomes in borderline dysplasia (BD) with AR have not been reported. Purpose: To report any differences in the management of the COS in BD and nondysplastic hips and to report comparative outcomes of BD with AR with matched controls with BD or AR (ie, focal pincer femoroacetabular impingement [FAI]). Study design: Cohort study; Level of evidence, 3. Methods: A multicenter matched-pair study was performed with data from a large prospectively collected database. Inclusion criteria were patients who had undergone primary unilateral hip arthroscopy including labral repair for FAI and/or chondral pathology without significant osteoarthritis (ie, Tönnis grade 0 or 1). The study group (BD+AR) was defined radiographically by lateral center-edge angle (LCEA) on standing anteroposterior pelvis of 18° to 25° and positive COS. A 1:1:1 matching on age, sex, and body mass index was performed with a control group with BD and another control group with AR (LCEA, >25°+COS). Acetabuloplasty rates were determined for each group. Mean 2-year outcomes including the 12-Item International Hip Outcome Tool (iHOT-12), minimally clinical important difference (MCID), substantial clinical benefit (SCB), and Patient Acceptable Symptom State (PASS) scores were compared. Subanalysis of the study group both with and without acetabuloplasty was performed. Results: There were 69 patients, with 23 in the study group and 23 in each control group. The effect of dysplasia with or without the presence of the COS resulted in changes in acetabuloplasty rates, with 0% performed in the BD group, 35% in the BD+AR study group, and 91% in the AR group ( P = .001). Arthroscopic outcomes demonstrated similar and significant mean 2-year improvement of iHOT-12 patient-reported outcomes, MCID, SCB, and PASS scores in the study and both control groups. There was a trend within the study group toward greater postoperative iHOT-12 scores in patients who received anterior-based acetabuloplasty than those who did not receive acetabuloplasty (81.7 and 70.4, respectively; P = .11). Conclusion: Acetabular coverage influences the management of the COS, with significantly lower acetabuloplasty rates in BD with AR compared with AR without BD (focal pincer impingement). Symptomatic patients with combined BD and AR had similar significant successful outcomes to those of patients with BD and those with AR (focal pincer impingement), whether treated without acetabuloplasty or, less frequently, with limited anterior-based acetabuloplasty.